Relationship of tannin levels and trypsin inhibitor activity with the in vitro protein digestibilities of raw and heat-treated winged bean (Phosphocarpus tetragonolobus) - Tan, Nget Hong; Wong, Kai Choo; De Lumen, Benito O. (American Chemical Society, 1984)
Three varieties of winged bean were heat processed in five different ways to determine the relationship among in vitro protein digestibility (IVPD), trypsin inhibitor activity (TIA), and assayable tannin. The IVPD of raw winged bean ranged from 68.8 to 72.9%. Heat treatments increased the IVPD to 76.0-90.7% and reduced both TLA and tannin. In terms of energy costs, 5-min autoclaving and quick cooking were the two most effective methods of improving IVPD. Dry heat (200 °C, 30 min) and direct boiling (20 min, no soaking) were least effective. Reductions in tannins and TIA did not necessarily result in proportional increases in IVPD.